Cracking the code of the Rohonc Codex. Issue 4 (4th July 2018) - Király, Levente Zoltán; Tokai, Gábor
ABSTRACT: The Rohonc Codex is a small 448-page codex handwritten in a script that has resisted deciphering since the codex was discovered in 1839. The main cause of this failure may be the fact, as we reveal, that the writing is not a substitution cipher (or "ancient alphabet") as most researchers presupposed but is in fact a code system with features that no codebreaker would expect, the breaking of which is an extremely heuristic task. This article is intended to be the first of three or four in which we summarize our findings made during our years-long research of the Rohonc Codex. In the present article we discuss general features of the text, our methodological criteria, and the story of cracking the code. To give weight to our argument we present several interlinear translations of passages from the codex's text. This will be expanded by further articles in which we plan to describe some advanced features of the code such as its morphology, syntax, and peculiarities, as well as the possible language(s) of the author; we will also provide a detailed table of contents, further indices, and a glossary.